Actual status of home care in a rural area in Aichi prefecture [Japan] - "Hayakawa, T; Hamada, S; Hayashi, K; Tsuzuki, M; Ikedo, M; Ando, T; Hayashi, M; Kawai, Y; Saiba, H; Suzuki, C. (JOURNAL OF THE JAPANESE ASSOCIATION OF RURAL MEDICINE, 2000)
"To clarify characteristics of home care in rural areas in Japan, we investigated the actual status of home care in a rural area (Asuke town, Asahi town, Inabu town, northern part of Toyota city and Shimoyama village) in Aichi prefecture. The subjects were 149 patients who were under medical care and nursing supervision at home for the last 2 years and a half. Age, sex, ADL, prognosis, principal care-givers of the patients and distance from patients' houses to our hospital were compared with the average data of all the nurse stations in Japan (1996). The percentage of patients over 90 years old was 23.4% in this area as against 13.5% of the national average. Sex and ADL levels were similar to the average. The proportion of females as principal care-givers of patients was 80%, which is about average. However, the proportion of daughters-in-law was 51.7%, double of the national average. In 48 cases (32%), the time required to get to the hospital by car was over 31 min. This ratio was 3 times higher than that of the average data, and it took 50 min from farthest patient's house (35km). In prognosis, 66 patients died-44 cases (67%) in hospital and 22 cases (23%) at home. Our questionnaire survey regarding patients' and care-givers' wishes was responded to by 38 of 47 principal care-givers who utilized our home care and nursing survice program. One half of care-givers were over 60 years old and had taken care of a patient for over 5 years. Mental stress, feeding and toileting were major problems most principal care-givers cited. However, they required services at a day-care institution for elderly patients and recovery of used paper diapers. Death at home was wished by 23 (61%) patients and care-givers, if they received enough medial care and welfare services. These findings revealed that elderly people take care of elderly patients, their houses are far from the hospital and they wish to die at home. More collaboration among all providers of medical care and health and welfare services, and the establishment of an information network are necessary to improve these problems, resulting in safe, acceptable and satisfied home care for patients and care-givers."